Exploitation of allochtonous raw materials in hunter-gatherer contexts. The archaeological sites of the Fagnano Lake, Tierra del Fuego, Argentina - de Angelis, Hernan Horacio (2015)
The exploitation of allochthonous raw materials has been registered in several archaeological sites of Isla Grande de Tierra del Fuego. The best known examples are those of green obsidian and glass. A new one is a silicified tuff identified at a site in the southern shore of Lake Fagnano, which comes from the Miraflores outcrop, located to the North of the island, more than 200 km away. Since the identification of this raw material in Kami 1 archaeological site, a techno-functional experimental program was carried out in order to identify Miraflores silicified tuff characteristics regarding manufacturing techniques, as well as behavior of edges for different utilization processes. Experimental tools were made on samples taken from the Miraflores outcrop and then used to work on various materials (wood, leather and bone). This article has two main purposes. The first one is to present the results obtained in the experimental study and the techno-morpho-functional analysis of lithic archaeological artifacts in silicified tuff from the southern shore of Lake Fagnano. The second is to discuss possible causes for selection of this raw material for the tool morphologies and uses identified in the site, as well as possible acquisition strategies implemented by hunter-gatherer societies of the central area of Tierra del Fuego.